2010
DOI: 10.1542/peds.2009-2795
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Ondansetron Is Associated With Lethal Outcome

Abstract: We report here the case of a child with a known muscular abnormality and susceptibility to malignant hyperthermia who abruptly died after receiving a therapeutic dose of ondansetron. Also, we discuss the pharmacodynamic relationship of ondansetron to malignant hyperthermia in a susceptible host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 16 publications
0
26
0
1
Order By: Relevance
“…Family counselling is vital to identify potentially MH-susceptible relatives [1] We performed a systematic literature review (including the patients in the studies mentioned above), based on a Pubmed search with "RYR1" and "rhabdomyolysis". This resulted in identification of several case report and small series [1,8,[21][22][23][24][25][26], and two review article [27,28] Subsequently, we also included cases from references of these articles [20,26,[29][30][31][32][33][34] and added our recent letter by Snoeck et al [35]. Finally, we added two patients from our paper on the spectrum of RYR1 related myopathies by Snoeck et al who were not included in any other publication (patients 14 and 52 [1]).…”
Section: Ryr1-related (Exertional) Rhabdomyolysis ((E)rm)mentioning
confidence: 99%
See 3 more Smart Citations
“…Family counselling is vital to identify potentially MH-susceptible relatives [1] We performed a systematic literature review (including the patients in the studies mentioned above), based on a Pubmed search with "RYR1" and "rhabdomyolysis". This resulted in identification of several case report and small series [1,8,[21][22][23][24][25][26], and two review article [27,28] Subsequently, we also included cases from references of these articles [20,26,[29][30][31][32][33][34] and added our recent letter by Snoeck et al [35]. Finally, we added two patients from our paper on the spectrum of RYR1 related myopathies by Snoeck et al who were not included in any other publication (patients 14 and 52 [1]).…”
Section: Ryr1-related (Exertional) Rhabdomyolysis ((E)rm)mentioning
confidence: 99%
“…physical exercise and hot ambient temperatures, or viral infection or exercise and medication. Gener et al reported the case of a child who had suffered a sevoflurane-triggered MH episode treated with dantrolene during an orchidopexy procedure (at the age of 3 years 5 months), a common operation during which MH episodes have been observed [32]. He died at the age of 5 and a half years when he developed muscle rigidity and became hyperthermic and asystolic after receiving ondansetron because of vomiting and abdominal pain [32].…”
Section: Box 2: Ryr1-related Exertional Rhabdomyolysis (Erm) In a 16-mentioning
confidence: 99%
See 2 more Smart Citations
“…Rarely, even deaths have been reported in adults and children. [3][4][5] Here, we report 2 cases of refractory cardiac arrest and death after administration of ondansetron in pediatric patients.…”
mentioning
confidence: 98%